Hazards of excessive use of bark mulch in green areas - Łukasiewicz, Szymon (Ecological Questions, 2014)
Bark mulch has been a popular additive in production and preparation of traditional garden soils. Being a porous material, it improves soil structure and ventilation. It has also become a valuable component of substrates, particularly for coniferous plants. Recently bark mulching of large areas has become increasingly common. The volume of bark mulch used for such purposes is very large. Bark is characterised by for high content of e.g. heavy metals, such as manganese, aluminum, zinc, cadmium or lead. After mineralization, elements introduced to soil will change its chemical composition, thus distorting the original balance of elements. This could lead to successive accumulation of those elements (Mn, Cd, Al, Zn, Pb) in soil, up to toxic levels.